Application of the adverse outcome pathway to identify molecular changes in prenatal brain programming induced by IUGR: Discoveries after EGCG exposure. (December 2022) - Kühne, Britta Anna; Teixidó, Elisabet; Ettcheto, Miren; Puig, Teresa; Planas, Marta; Feliu, Lidia; Pla, Laura; Campuzano, Victoria; Gratacós, Eduard; Fritsche, Ellen; Illa, Miriam; Barenys, Marta
Abstract: Following a multi-disciplinary approach integrating information from several experimental models we have collected new evidence supporting, expanding and redesigning the AOP "Disrupted laminin/int-β1 interaction leading to decreased cognitive function". Investigations in vitro in rabbit and rat neurospheres and in vivo in mice exposed to EGCG (epigallocatechin-gallate) during neurodevelopment are combined with in vitro evaluations in neural progenitor cells overexpressing int-β1 and literature information from int-β1 deficiency models. We have discovered for the first time that neural progenitor cells from intrauterine growth restricted (IUGR) animals overexpress int-β1 at gene and protein level and due to this change in prenatal brain programming they respond differently than control neurospheres to the exposure of EGCG, a compound triggering neural progenitor cell migration alterations. We have also identified that EGCG developmental exposure has deleterious effects on neuronal branching and arborization in vitro and in vivo . Our results warn that a thorough developmental neurotoxicity characterization of this and other catechin-based food supplements is needed before recommending their consumption during pregnancy.